2002
DOI: 10.1046/j.1365-2648.2002.02214.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of part‐time post‐registration degrees on practice

Abstract: The clinical effectiveness of education initiatives depends on the learners, the course and the workplace. To maximize the benefits accruing to patients from continuing professional education and role expansion, further exploration of the contribution of higher education programmes to clinical practice is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 64 publications
6
75
2
Order By: Relevance
“…(Hardwick & Jordan, 2002;Francke et al, 1995;Sheperd, 1995;Waddell, 1992). Significantly, EBL learning groups were identified as central to the development of these skills as well as a font for more information.…”
Section: Ebl As a Way Of Learning For Nursingmentioning
confidence: 99%
“…(Hardwick & Jordan, 2002;Francke et al, 1995;Sheperd, 1995;Waddell, 1992). Significantly, EBL learning groups were identified as central to the development of these skills as well as a font for more information.…”
Section: Ebl As a Way Of Learning For Nursingmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The latter includes upgrading an initial qualification; keeping abreast with global and local developments in the profession; gaining promotion; enhancement of their career; improving knowledge and performance at work; seeking academic credibility; and taking forward the profession to enhance care. [2,[4][5][6][9][10][11] Spencer [6] undertook a study to examine personal reasons for undertaking Masters study and found that a large majority of participants did so to intellectually stimulate themselves and to keep up to date with nursing development. Free fees also act as an incentive; gaining access to a speciality through degree study; and "professional survival" are classed as major reasons for undertaking a degree postqualification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[5,12] A major reason for nurses applying for and undertaking post registration courses is they perceive it will make a difference to practice and examples to evidence this are speculative and unsubstantiated. [2,6,7] Much of the research refers to nurses' self-perception of their value, post degree. [7] This should not be underestimated as improvements in personal confidence, cognitive functioning, and evidence based practice development may positively influence patient care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This evidence could also be used to inform purchasing decisions and curriculum development (Jordan et al, 1999). A continuing lack of such evidence may deter future investors in the current political and economic climate (Hardwick and Jordan, 2002).…”
mentioning
confidence: 99%